Surface structures of thermoplastic and thermoset films after modification by graft copolymerization: Comparative study by x-ray photoelectron spectroscopy and atomic force microscopy - Loh, F.C. (2014)
Journal of Vacuum Science and Technology B: Microelectronics and Nanometer Structures